Kontroversi Hak Asasi Manusia Antara Paham Universal dan Paham Partikular - Azmi Syahputra (KEADILAN PROGRESIF, 2011)
The debate about human rights always interesting  from the stakeholder, it is about understanding of universal and particular perspectire of humdn rights, experience long  debate.Because second understand base on different  opinion between one wiith another the universal perspective understanding that provided in opinion has individual (liberalism), is the particular perspective understanding being provided in opinion has communal (sociality). The debate behween understanding universal and particular perspective to concern of human rights, final end at Wina Conference Year 1993 (produce wina Declaration and action program), where entrants Conference world, not again polarize to understand universal and particular perspective, unanimously get to understanding universality of human rights, but in the implementation is  accustommed with condition social cultural from nations and state.